Gallbladder Agenesis with Refractory Choledocholithiasis - Jamie Tjaden; Kevin Patel; Aziz Aadam (Case Reports in Gastrointestinal Medicine)
Congenital agenesis of the gallbladder is a rare anomaly which is usually asymptomatic and found incidentally. In some cases, however, patients are symptomatic. Common symptoms include right upper quadrant abdominal pain, nausea, and vomiting. Jaundice is present in some symptomatic cases and is due to associated choledocholithiasis (Fiaschetti et al. 2009). In this case, a 63-year-old female presents with jaundice and episodic right upper quadrant abdominal pain with nausea and vomiting. Bilirubin and alkaline phosphatase were found to be markedly elevated. Upper endoscopic ultrasound (EUS) revealed choledocholithiasis, and the patient required multiple endoscopic retrograde cholangiopancreatography (ERCP) sessions before successful extraction of all stones. Subsequent surgical exploration revealed congenital agenesis of the gallbladder. Although this is a rare finding, patients with agenesis of the gallbladder are at increased risk of developing de novo choledocholithiasis which may be challenging to extract.